Silly 123s - Gallup, Joan (Philadelphia : Running Press Book Publishers, 2002)
"This wonderfully engaging book asks young children to locate and count an assortment of objects placed in scenes with silly animals. It presents reproductions of eleven spectacular double-spread oil paintings framed with Joan Gallup's unique sculpted clay borders, along with plenty of her charming characters and creations. This beautiful gift edition is designed to become a childhood favorite!" - Library Thing
B
b
b